FORECAST OF CRUDE OIL PRODUCTION OUTPUT IN AN OIL FIELD IN THE NIGER DELTA REGION OF NIGERIA - Chinedum Mgbemena; Emmanuel Chinwuko (International Journal of Industrial Engineering and Production Research, 2020)
Crude oil production output forecast is very important in the formulation of genuine and suitable production policies; it is pivotal in planning and decision making. This paper explores the use of forecasting techniques to assist the oil field manager in decision making. In this analysis, statistical models of projected trends which involves graphical, least squares, simple moving average and exponential smoothing methods were compared. The least squares method was found to be most suitable to capture the recent random nature of crude oil production output in the oilfield of the Niger Delta region of Nigeria. In addition, a multiple linear regression model was developed for predicting daily, weekly, monthly or even yearly volume of crude oil production output in the oilfield facility.